2015
DOI: 10.1039/c4ra16687f
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature chlorobenzene catalytic oxidation over MnOx/CNTs with the assistance of ozone

Abstract: Manganese oxide supported on carbon nanotubes (MnO x /CNTs) were prepared by an impregnation method and their catalytic oxidation performances of chlorobenzene (CB) with the assistance of ozone were investigated. The experimental results indicated a synergistic effect between the MnO x /CNTs catalyst and ozone promotion for CB destruction, which promoted CB oxidation at temperatures between 80 C and 280 C. Especially at temperatures below 120 C, both CB conversion and CO 2 selectivity above 95% were achieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The results suggested that ozone efficiently promoted CB catalytic oxidation over MnO x /CNT catalysts, and CO 2 selectivity above 95% could be achieved at 80 °C (GHSV = 36 000 h –1 ). Moreover, MnO x /CNT catalysts showed good stability and resistance to Cl poisoning in the presence of ozone . The promotion effect of ozone on CB oxidation over CuO x /CNT materials was also reported …”
Section: Influence Of Reaction Conditionsmentioning
confidence: 84%
See 2 more Smart Citations
“…The results suggested that ozone efficiently promoted CB catalytic oxidation over MnO x /CNT catalysts, and CO 2 selectivity above 95% could be achieved at 80 °C (GHSV = 36 000 h –1 ). Moreover, MnO x /CNT catalysts showed good stability and resistance to Cl poisoning in the presence of ozone . The promotion effect of ozone on CB oxidation over CuO x /CNT materials was also reported …”
Section: Influence Of Reaction Conditionsmentioning
confidence: 84%
“…Moreover, MnO x /CNT catalysts showed good stability and resistance to Cl poisoning in the presence of ozone. 1061 The promotion effect of ozone on CB oxidation over CuO x /CNT materials was also reported. 1076…”
Section: Promotion Effect Of Ozonementioning
confidence: 95%
See 1 more Smart Citation
“…Catalysts plus adsorbents (e.g., activated carbon [4,5], zeolite [6,7], and grapheme [8]) have been proven to improve the catalytic activity by capturing more reactants onto the catalyst surface for further decomposition. CNTs are one of the excellent adsorbents for chloro-aromatic compounds [5,9] and its introduction effectively elevates the low temperature catalytic activity of several composites catalysts [10][11][12], because the presence of CNTs can: (1) enlarge the adsorption capacity and adsorption affinity of catalysts [11,12]; (2) parallelly adsorb the chloro-aromatic compounds onto the surface of CNTs [13,14]; (3) optimize the physicochemical properties of composites catalysts [10,15]. However, our previous study [15] indicated that V/Ti-CNTs catalyst achieves almost total removal of chloro-aromatic compounds mainly due to the adsorption rather than real decomposition at 150 C. Therefore, the decomposition of the adsorbed reactants needs to be further accelerated when CNTs-containing composite catalyst is used in treating chloroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…5 Ozone, characterized by long life time, strong oxidation ability, short reaction time, and large scale production, has always been regarded as the preferred oxidizing agent. 25,26 However, the relatively high investment and running cost are becoming the biggest obstacles in promoting this technique. 27 Therefore, catalysts are introduced to improve the oxidation efficiency with low ozone usage.…”
Section: Introductionmentioning
confidence: 99%